Impact of Transformational Leadership and Transactional Leadership on Commitment to Change: Moderating role of Organizational Culture - Butt, Nabeed; Afzal, Syed Muhammad Numan; Aslam, Rashid Ali; Ali, Shahzad (Pakistan Journal of Humanities and Social Sciences, 2023)
Businesses need to be less watchful and more focused on conduct if they are to succeed and remain competitive in the market. This study's goal is to investigate how transactional leadership and transformational leadership affect workers' commitment to change at knowledge intensive sector. Through the use of questionnaires and a non-probability convenient sampling technique, information was gathered from 500 employees. Techniques for statistical analysis include Structural equation modeling and Confirmatory factor analysis. Results signified that transformational leadership and transaction leadership has significant effect of an employee’s credibility. Moreover, organizational culture significantly moderate on the connection between commitment to change and leadership styles (transformational and transactional).